2024
DOI: 10.2807/1560-7917.es.2024.29.7.2300318
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of antimicrobial resistance of Mycoplasma genitalium, Belgium, 2022

Irith De Baetselier,
Hilde Smet,
Kaat Kehoe
et al.

Abstract: Background Antimicrobial resistance (AMR) of Mycoplasma genitalium (MG) is a growing concern worldwide and surveillance is needed. In Belgium, samples are sent to the National Reference Centre of Sexually Transmitted Infections (NRC-STI) on a voluntary basis and representative or robust national AMR data are lacking. Aim We aimed to estimate the occurrence of resistant MG in Belgium. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Moreover, in a recent study conducted in Belgium, De Baetselier et al [16] reported a significant prevalence of macrolide-resistant M. genitalium across various populations in Belgium. Specifically, among men, 72.4% of the samples analysed in the study exhibited genotypic resistance to macrolides [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, in a recent study conducted in Belgium, De Baetselier et al [16] reported a significant prevalence of macrolide-resistant M. genitalium across various populations in Belgium. Specifically, among men, 72.4% of the samples analysed in the study exhibited genotypic resistance to macrolides [16].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in a recent study conducted in Belgium, De Baetselier et al [16] reported a significant prevalence of macrolide-resistant M. genitalium across various populations in Belgium. Specifically, among men, 72.4% of the samples analysed in the study exhibited genotypic resistance to macrolides [16]. Despite the study's limited sample size, all specimens obtained from MSM displayed mutations associated with macrolide resistance, likely attributed to the use of macrolides in treating other STIs or unrelated infections [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation